The economy of colonial Malaya administrators versus capitalists - Raja, Sivachandralingam Sundara (Routledge studies in the modern history of Asia)
"Although colonies are often viewed as having been of crucial economic importance to Britain's empire, those responsible for administering the colonies were often not at all interested in or supportive of commercial ventures, as this book demonstrates. Based on extensive original research, and including detailed case studies of the agricultural and mining sectors in late nineteenth and early twentieth century Malaya, the book examines how administrators and capitalists interacted, showing how administrators were often hostile to business and created barriers to business success. It discusses in particular contradictory colonial government policies, confusion over land grants and conflicts within bureaucratic hierarchies, and outlines the impact of such difficulties, including the failure to attract capital inflows and outright business failures. Overall, the book casts a great deal of light on the detail of how business and government actually worked in Britain's colonial empire"